Fatigue and Sleep Quality Among Staff Nurses Working in A Tertiary Care Hospital During COVID-19 Pandemic - Rana, Sunita; Koirala, Mamta; Thapa, Nongmaithen Jid Noon Baral; KC, Samikshya (Journal of Lumbini Medical College, 2021)
Introduction: Fatigue, a universal phenomenon, is a suboptimal psychophysiological condition caused by physical and/or mental exertion. Insufficient recovery between work shifts causes accumulated acute fatigue to progress into chronic. As fatigue and sleep quality are related, adequate sleep and inter shift recovery are thus vital to the overall health. The current COVID-19 pandemic has caused added burden to the nursing workforce worldwide. This study aimed to assess fatigue and sleep quality among staff nurses of a tertiary care hospital during the pandemic. Methods: A descriptive cross-sectional study was conducted among 151 staff nurses of Lumbini Medical College and Teaching Hospital (LMCTH) using enumerative sampling method. Valid and reliable instruments i.e., Occupational Fatigue Exhaustion Recovery (OFER) and Pittsburgh Sleep Quality Index (PSQI) were used. Analysis was done using descriptive and inferential statistics. Results: The mean ±SD age of the participants was 26.54±6.93 years. Less than half (39.1%) of them had moderate to high acute fatigue. Nearly half (41.2%) had high chronic fatigue and most (61.6%) had low to moderate inter shift recovery. Poor sleep was found among 60.9% of the participants with mean global PSQI score of 6.74. Sleep quality had moderate positive correlation with chronic (r=0.4, p<0.001) and acute (r=0.39, p<0.001) fatigue whereas had moderate negative correlation with inter shift recovery (r=- 0.41, p<0.001) which were statistically significant. Conclusion: The staff nurses had fatigue and poor sleep during COVID-19 pandemic. Nursing administration should take appropriate measures timely to decrease fatigue and improve sleep to prevent serious consequences.